2015
DOI: 10.1038/srep14256
|View full text |Cite
|
Sign up to set email alerts
|

Genetic responses to seasonal variation in altitudinal stress: whole-genome resequencing of great tit in eastern Himalayas

Abstract: Species that undertake altitudinal migrations are exposed to a considerable seasonal variation in oxygen levels and temperature. How they cope with this was studied in a population of great tit (Parus major) that breeds at high elevations and winters at lower elevations in the eastern Himalayas. Comparison of population genomics of high altitudinal great tits and those living in lowlands revealed an accelerated genetic selection for carbohydrate energy metabolism (amino sugar, nucleotide sugar metabolism and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 57 publications
3
40
1
1
Order By: Relevance
“…Analysis using genome sequencing and ChIP has shown that the ITGA2 gene assists hypoxic adaptation in Tibetan pigs and great tits in the highlands (Ai et al, 2014; Qu et al, 2015). In the present study, ITGA2 was down-methylated in promoter regions, resulting in the upregulation of gene expression in TC compared to CH.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis using genome sequencing and ChIP has shown that the ITGA2 gene assists hypoxic adaptation in Tibetan pigs and great tits in the highlands (Ai et al, 2014; Qu et al, 2015). In the present study, ITGA2 was down-methylated in promoter regions, resulting in the upregulation of gene expression in TC compared to CH.…”
Section: Discussionmentioning
confidence: 99%
“…Gene families were identified using TreeFam (Li et al, 2006) with default settings from 16 animal genomes [bar-headed goose (Anser indicus), swan goose (Anser cygnoides) (Lu et al, 2015), crested ibis (Nipponia nippon) , mallard (Anas platyrhynchos) (Huang et al, 2013), red junglefowl (Gallus gallus) (International Chicken Genome Sequencing Consortium, 2004), turkey (Meleagris gallopavo) (Dalloul et al, 2010), common cuckoo (Cuculus canorus) (https://www.ncbi.nlm.nih.gov/assembly/GCF_000709325.1/), rock pigeon (Columba livia) (Shapiro et al, 2013), ground tit (Pseudopodoces humilis) (Qu et al, 2013), bananaquit (Coereba flaveola) (Antonides, Ricklefs & DeWoody, 2017), great tit (Parus major) (Qu et al, 2015), zebra finch (Taeniopygia guttata) (Warren et al, 2010), ruff (Philomachus pugnax) (Lamichhaney et al, 2016), peregrine falcon (Falco peregrinus) (Zhan et al, 2013), yak (Bos mutus) (Qiu et al, 2012) and tibetan antelope (Pantholops hodgsonii) (Ge et al, 2013)]. A total of 2,888 single-copy orthologs, shared by these 16 species, were finally identified.…”
Section: Comparative Genome Analysismentioning
confidence: 99%
“…Understanding how vertebrates cope with these harsh conditions can provide important insights into the process of adaptive evolution (Zhang et al, 2016a;Zhang et al, 2016b). Among the high-altitude-adapted vertebrates, birds in general have excellent hypoxia tolerance and can maintain the highest basal metabolic rates during hypoxia too severe for most mammals to survive (Tucker, 1968;Faraci, 1991;Monge & Leon-Velarde, 1991), and are therefore especially compelling subjects for studies of high-altitude adaptation (Projecto-Garcia et al, 2013;Qu et al, 2013;Qu et al, 2015;Zhu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…MAPK1 has been reported to be involved in accelerated selection in the highland great tit during the hypoxia adaptation [21]. MAPK1 only bound to miR-19b-3p of the 14 miRNAs predicted by both TargetScan and miRanda software.…”
Section: Resultsmentioning
confidence: 99%
“…In the southwestern mountains (SWM), the great tit is distributed between 2000 and 4500 meters above sea level. The high-altitude population of great tits shows an accelerated genetic selection for carbohydrate energy metabolism and the hypoxia response (e.g., the MAPK signaling pathway) compared to lowland populations [21]. Due to the crucial role of the MAPK signaling pathway in the hypoxia response in the great tit, we chose MAPK1 as a candidate gene.…”
Section: Introductionmentioning
confidence: 99%